BASED ON THE WORKS OF EASTERN THINKERS DEVELOPMENT OF MORAL QUALITIES IN STUDENTS (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article presents the views of thinkers on the development of moral qualities in students. The categories of morality are listed.